Is It Interests, Ideas or Institutions? Explaining Elected Representatives' Positions Toward Democratic Innovations in 15 European Countries - Junius, Nino; Matthieu, Joke; Caluwaerts, Didier; Erzeel, Silvia (Frontiers in Political Science, 2020)
In response to the alleged legitimacy crisis, representative democracies have in recent years witnessed increased demands for democratic innovations aimed at giving citizens a more direct say in decision-making. Such initiatives, however, often rock the foundations of the model of representative democracy which assumes a more indirect link between citizens and political decisions, and which puts political power more firmly in the hands of elected representatives. In this paper, we study how these elected members of parliament (MPs)–who are key actors in representative democracy, yet potentially see their role reduced in deliberative or participatory models of democracy–think about democratic innovations. We study to what extent and why they support two common types of democratic innovations, namely referendums and deliberative events. While it is generally assumed that MPs' positions toward these initiatives are driven by their ideological predispositions, we propose and test a comprehensive framework which considers the role played by 3 “I's”: ideas, interests and institutions. Using original data from the PARTIREP MP survey, this paper maps variations in MPs' preferences for democratic innovations across 15 European countries, and shows that these variations can be explained by differences in MPs' ideological (left/right) views, legitimacy perceptions and role conceptions, their strategic position in government or opposition, and their electoral incentives. The 3I framework predicts MPs' support for both types of innovations, but more strongly so for referendums than for deliberative events.